Hybrid work as a determinant of employee job satisfaction through work-life balance in Dompet Dhuafa - Iqbal; Indri Guslina; Asep Hendriana (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2026)
Hybrid work has become a widely adopted flexible work arrangement; however, its impact on job satisfaction through work life balance remains inconsistent, particularly in non profit organizations. This study aims to examine the effect of hybrid work on job satisfaction and the mediating role of work life balance at Dompet Dhuafa.This study employs a quantitative approach using Partial Least Squares Structural Equation Modeling. Data were collected from 110 employees through purposive sampling. The results show that hybrid work has a positive and significant effect on job satisfaction and work life balance. However, work life balance does not significantly affect job satisfaction and does not mediate the relationship. These findings highlight the context dependent role of work life balance and provide practical insights for designing effective hybrid work systems.